Adoption of the Case Method of Professional Nursing Care Management in the Delivery Room: A Qualitative Study - Aminah Aminah; Gunarmi Gunarmi; Bima Suryantara (GLOBAL HEALTH SCIENCE GROUP, 2025)
The background of this study focuses on improving the quality of midwifery services at Dr. Abdul Aziz Regional General Hospital (RSUD Singkawang) through the adoption of the Professional Nursing Care Management (MAKP) case method. Research Methods: This study used a qualitative approach and a case study design to explore the application of this method in the delivery room. Research informants included the Head of the Delivery Room and midwives on duty at Dr. Abdul Aziz Regional General Hospital (RSUD Singkawang) as many as 16 midwives. Data collection used in this study included interviews, observation, and documentation. Thematic analysis was used for data analysis. This thematic analysis process resulted in a list of themes from the coding results. The results showed that the head of the room acts as a first-line manager, responsible for planning, organizing, directing, and supervising, which is delegated to BP4 or BP3 midwives when needed. The service ratio is set at 1 midwife to 1:3 patients, in accordance with the midwife's clinical authority. Shift scheduling is flexible, with a minimum of one BP3 midwife per shift. The process of admitting new patients and handovers is carried out with a 1:1 patient-to-midwife ratio. Discharge planning is carried out collaboratively with the patient and the healthcare team. There are two types of documentation, electronic and manual, completed by the midwives. The conclusion of this study indicates that the MAKP case-based method can be implemented in the delivery room by considering the midwife's clinical authority in accordance with the specified authority details.